Influence of Light Stress on the Accumulation of Xanthophylls and Lipids in Haematococcus pluvialis CCALA 1081 Grown under Autotrophic or Mixotrophic Conditions - Doria, Enrico (2018)
The influence of light stress and trophic environmental conditions on the production of astaxanthin, other xanthophylls and lipids from an Argentinian strain of Haematococcus pluvialis was investigated. Microalgae cultures were incubated for two weeks in autotrophic or mixotrophic conditions (with sodium acetate in the culture medium) and subjected to two different light stresses. HPLC analyses showed that: 1) regardless of the growth conditions, microalgal cells accumulated most of the astaxanthin (about 90%) in esterified form; 2) maximal increase of astaxanthin level was observed in the culture grown in autotrophic conditions subjected to moderate light stress (90 μmol photons m-2 s-1), while the same light regime in mixotrophic conditions led to a lower increase (only 25.8 fold); 3) in the case of high light stress (350 μmol photons m-2 s-1), the adaptive response of microalgae also led to a significant increase in the amount of astaxanthin both in autotrophic (22 fold increase) and in mixotrophic (16 fold increase) conditions; 4) an inverse correlation (R2 = 0.977) exists between the amount of lipids and that of astaxanthin accumulated by Haematococcus grown under different growth conditions; 5) lutein was found to be the most accumulated pigment in microalgae not subjected to light stress.